Grandmothers as gatekeepers? The role of grandmothers in influencing health-seeking for mothers and newborns in rural northern Ghana. - Gupta, M.L.; Aborigo, R.A.; Adongo, P.B.; Rominski, S.; Hodgson, A.; Engmann, C.M.; Moyer, C.A. (Global Public Health, 2015)
Previous research suggests that care-seeking in rural northern Ghana is often governed by a woman's husband or compound head. This study was designed to explore the role grandmothers (typically a woman's mother-in-law) play in influencing maternal and newborn healthcare decisions. In-depth interviews were conducted with 35 mothers of newborns, 8 traditional birth attendants and local healers, 16 community leaders and 13 healthcare practitioners. An additional 18 focus groups were conducted with stakeholders such as household heads, compound leaders and grandmothers. In this region, grandmothers play many roles. They may act as primary support providers to pregnant mothers, care for newborns following delivery, preserve cultural traditions and serve as repositories of knowledge on local medicine. Grandmothers may also serve as gatekeepers for health-seeking behaviour, especially with regard to their daughters and daughters-in-law. This research also sheds light on the potential gap between health education campaigns that target mothers as autonomous decision-makers, and the reality of a more collectivist community structure in which mothers rarely make such decisions without the support of other community members.
Keywords: Ghana; grandmothers; health-seeking behaviour; maternal and child health; power dynamics